Komunikasi Terapeutik Perawat dan Tingkat Kecemasan Pasien Suspek Covid-19 - Lina Indrawati; Emilia Wahyuningsih; Hilda Meriyandah Agil (FORIKES, 2022)
Stress and anxiety are normal feelings when facing a crisis like the Covid-19 pandemic, especially for patients who are hospitalized. One of the factors that can reduce the patient's anxiety level is therapeutic communication. The more information you get, the less worried you will be, which in turn will reduce anxiety. This study aims to determine the relationship between nurses' therapeutic communication and the anxiety level of patients with suspected Covid-19. The design of this study was cross-sectional, involving 27 patients selected by convenient sampling technique. The independent variable is therapeutic communication and the dependent variable is anxiety level. Measuring tool was a questionnaire and data were analyzed using the Chi Square test. The results of the statistical test showed a p value of 0.000, which indicated that there was a relationship between nurse therapeutic communication and anxiety levels in suspected Covid-19 patients in the Covid-19 Suspect Room, Cibitung Medika Hospital.Keywords: therapeutic communication; anxiety level; Covid-19 ABSTRAK Stress dan cemas adalah perasaan yang normal saat menghadapi krisis seperti pandemik Covid-19, terutama bagi pasien yang dirawat di rumah sakit. Salah satu faktor yang dapat menurunkan tingkat kecemasan pasien yaitu komunikasi terapeutik. Semakin banyak informasi yang didapatkan, maka kekhawatiran akan berkurang, yang akhirnya akan menurunkan kecemasan. Penelitian ini bertujuan untuk untuk mengetahui hubungan antara komunikasi terapeutik perawat dengan tingkat kecemasan pasien suspek Covid-19. Rancangan penelitian ini adalah cross-sectional, dengan melibatkan 27 pasien yang dipilih dengan teknik convenient sampling. Variabel independen adalah komunikasi terapeutik dan variabel dependen adalah tingkat kecemasan. Alat ukur adalah kuesioner dan data dianalisis menggunakan uji Chi Square. Hasil uji statistik menunjukkan nilai p 0,000, yang menunjukan bahwa ada hubungan komunikasi terapeutik perawat dengan tingkat kecemasan pada pasien suspek Covid- 19 di Ruang Suspek Covid-19, Rumah Sakit Cibitung Medika.Kata kunci: komunikasi terapeutik; tingkat kecemasan; Covid-19